Alkaloid production of Solanum elaeagnifolium Cav from callus for anticancer potential using gene expression of cancer-related genes - Abdulkarim Dakah; Iyad Musallam; Raida Wajih Khalil (PLoS ONE, 2025)
Cancer is one of the major diseases that threaten human life and causes death for many people worldwide. Some alkaloids derived from plants show promising potential for cancer treatment. Solanaceae family is of these plants that have promising alkaloid. In this study alkaloid production from Solanum elaeagnifolium callus cultures was investigated and their anticancer properties were evaluated. Optimal callus growth and alkaloid production were achieved in media enriched with a combination of BAP and 2,4-D at a ratio of 1.0:1.0 mg/L. LC-MS/MS analysis showed that β-Solamargine, tomatidenol, Solasonine, solanidine and solasodine are the most important alkaloids of Solanum elaeagnifolium. Moreover, the analysis revealed that β-Solamargine is the predominant alkaloid (78.7%) in callus extracts. The results of MTT assay, demonstrated that the most effective response were obtained from callus extracts medium containing a balanced concentration of BAP and 2,4-D, and it yielding an IC50 of 6.25 µl/ml. In contrast, lower efficacy was observed with IC50 values of 25 and 50 µl/ml, when callus medium were supplemented with NaCl and yeast extract, respectively. Gene expression analysis shows an increase in the Bax/Bcl-2 ratio following 24 h of the extracts treatment. Along with a down regulation of CDK1 gene expression in comparison to untreated MCF7 cells, the CDK1 levels were elevated. Alkaloids derived from S. elaeagnifolium may be a promising candidate for anticancer therapy; further investigation is needed in vivo.